Exploration of Phinisi Ship Components as a Source for Learning Elementary School Geometry: Ethnomathematics Study - Ady Akbar; Tatang Herman; Didi Suryadi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Mathematics is still seen as a non-cultural subject. Mathematics and culture are two aspects that have a strong relationship. Culture provides a natural means for students to access a framework for conceptual understanding in mathematics. One of the important cultural objects in Indonesia is the Phinisi. The phinisi is a traditional wooden ship originating from Bulukumba Regency, South Sulawesi province which is recorded as a world cultural heritage. This study explores the concept of ethnomathematics geometry on phinisi ships. The method used in this research is an exploratory-descriptive method through an ethnographic approach to explain and analyze the ethnomathematical concepts of geometry on the components of the phinisi. Research data were collected through a literature review, direct observation of the shape and process of making phinisi, and interviews with expert phinisi shipbuilders. The results showed that there are geometric ethnomathematical concepts in the form of flat shapes and spatial shapes on several phinisi components. This ethnomathematical concept is relevant to the formal mathematical concepts learned in school so it has the potential to be a source of learning mathematics.